Oxygen vacancy enhanced photocatalytic activity of Cu2O/TiO2 heterojunction - Hong Qian; Binxia Yuan; Yuhao Liu; Rui Zhu; Weiling Luan; Chengxi Zhang (iScience, 2024)
Summary: In this study, a method was developed to create oxygen vacancies in Cu2O/TiO2 heterojunctions. By varying the amounts of ethylenediaminetetraacetic acid (EDTA), sodium citrate, and copper acetate, Cu2O/TiO2 with different Cu ratios were synthesized. Tests on CO2 photocatalytic reduction revealed that Cu2O/TiO2’s performance is influenced by Cu content. The ideal Cu mass fraction in Cu2O/TiO2, determined by inductively coupled plasma (ICP), is between 0.075% and 0.55%, with the highest CO yield being 10.22 μmol g−1 h−1, significantly surpassing pure TiO2. High-resolution transmission electron microscopy and electron paramagnetic resonance studies showed optimal oxygen vacancy in the most effective heterojunction. Density functional theory (DFT) calculations indicated a 0.088 eV lower energy barrier for ∗CO2 to ∗COOH conversion in Cu2O/TiO2 with oxygen vacancy compared to TiO2, suggesting that oxygen vacancies enhance photocatalytic activity.